Effect of Jogging Program on Midwives' Physical Fitness: A Randomized, Controlled Trial - Minoo Safaei; Zahra Abedian; Seyed Reza Mazloum; Seyed Reza Attarzadeh Hosseini (Mashhad University of Medical Sciences, 2014)
Background & aim: Background & aim: Physical fitness is essential for maintaining optimal health and can be achieved and improved by doing physical activities. Maximal oxygen consumption (VO2 max) has been used as a measure of physical fitness. This study aimed to determine the effect of jogging program on midwives' physical fitness. Methods:In this randomized controlled trial two large healthcare centers in Mashhad were randomly selected and each center assigned to either intervention or control group. 60 employed midwives, working at these centers, were selected via convenience sampling. The intervention group performed aerobic exercises at 30-60% VO2 max during 24 sessions. At the beginning and end of the study, participants' physical fitness was measured  by calculating VO2 max, using Bruce test. Independent t-test, paired t-test, Mann-Whitney U, Wilcoxon, and Chi-square tests were carried out using SPSS version 19 to analyse data.  Results: The two groups showed no significant difference in terms of age, marital status, level of education, economic status and body mass index (P>0.05). Mean VO2 max in the intervention group (30.6±9.1) was significantly higher than that of the control group (24.3±7.3) (P=0.023). Participants' physical fitness was increased up to 30% by jogging. Conclusion:As the results indicated, jogging could improve midwives' physical fitness. Therefore, it is essential that health system directors pay more attention to providing facilities at every workplace in order to improve employees' physical fitness.